Bi-directional continuous wave doppler flowmeter and its application in investigations of disturbed blood flows - PIECHOCKI, Maciej (Archives of Acoustics, 1986)
The paper deals with a new two-way Doppler apparatus and with its clinical applications. A mathematical description is given of operations leading to the separation of a signal in dependence of the flow direction. Also a block diagram of an analogue realization of such a system, and a diagram of a broad-band phase shifter, which is the principal part of the system, are presented. The part of the paper dealing with the applications shortly presents diagnostic methods and new clinical applications of flowmeters, in. which the system of separating flow directions plays a significant part.